Fusarium oxysporum as the causal agent of vascular wilt in Ruta graveolens L. in Colombia - Perdomo, Tatiana Vanessa Perdomo; Güisa, Diego Herney; Moreno-López, Jenny Paola (Revista de Ciencias Agrícolas, 2024)
The increasing demand for rue (Ruta graveolens L.), widely used for medicinal and aromatic purposes, has fostered the social development of farmers in the Village of San Raimundo Alto, in Granada, Cundinamarca, where small producers cultivate this plant. However, vascular wilt is a major phytosanitary problem, causing plant death, reduced production, and economic losses. The causal agent of this disease had not been previously identified in Colombia. This study aimed to identify the pathogen responsible for vascular wilt in rue. Symptomatic plants were collected from the Village of San Raimundo Alto and analyzed in the phytopathology laboratory of Universidad de Cundinamarca. For the isolation, twenty-four rue plants of two different ages (45 and 90 days after sowing) were processed. Morphological identification of the isolated fungi was performed considering macroscopic and microscopic characteristics. The Fusarium genus was found in all isolates, and it was verified by the fulfillment of Koch’s postulates that the fungus that causes the vascular wilt of rue plants was Fusarium sp. For molecular analysis of pathogenic isolates, DNA extraction was performed, and primers of internal transcribed spacers—ITS (ITS4 and ITS5) and elongation factor—TEF (EF1 and EF2) were used for polymerase chain reaction (PCR). The sequences obtained were compared with those deposited at the GenBank database (NCBI), identifying all isolates analyzed as Fusarium oxysporum, with identity percentages greater than 98%. To our knowledge, this is the first report in Colombia of this pathogen causing vascular wilting in rue.